Replication timing and transcriptional control: beyond cause and effect — part III. (June 2016) - Rivera-Mulia, Juan Carlos; Gilbert, David M
Abstract : DNA replication is essential for faithful transmission of genetic information and is intimately tied to chromosome structure and function. Genome duplication occurs in a defined temporal order known as the replication-timing (RT) program, which is regulated during the cell cycle and development in discrete units referred to as replication domains (RDs). RDs correspond to topologically-associating domains (TADs) and are spatio-temporally compartmentalized in the nucleus. While improvements in experimental tools have begun to reveal glimpses of causality, they have also unveiled complex context-dependent relationships that challenge long recognized correlations of RT to chromatin organization and gene regulation. In particular, RDs/TADs that switch RT during development march to the beat of a different drummer.